How Visitor Satisfaction and Intention to Revisit Are Created by Event Quality and Perceived Value? A Lesson from the Local Food Festival in Brebes - Andi Yulianto; Roby Setiadi; Herniah Herniah (School of Business, IPB University (SB-IPB), 2023)
The emergence of many festivals and events shows that Arranging festivals centered around specific themes has the potential to boost economic development on both local and national scales. To investigate how events can improve visitors' perception of event quality, perceived value, trust, visitor satisfaction, and behavioral intentions, the annual food festival during the 344th anniversary celebration of Brebes was selected to explore these relationships. A total of 350 questionnaires were distributed to visitors and the data analysis was performed on 335 valid questionnaires using structural equation modeling. The results show that event quality has a positive and significant effect on perceived value (β = 0.205; p-value 0.037 <0.05). In addition, perceived value has a positive and significant effect on trust (β = 0.0585; p-value 0.000 <0.05). Finally, trust has a positive impact on event satisfaction (p-value 0.000 <0.05), which in turn affects the intention to revisit (p-value 0.004 <0.05). Drawing from these observed outcomes, this research provides practical and theoretical insights for event management entities and festival organizers to continue hosting annual theme-centered festivals during specific occasions and destinations to improve visitors' attachment to the values and authenticity offered. Keywords: event quality, event satisfaction, intention to revisit, perceived value, food festival